Preemergence and Post-Harvest Kochia Control in Wheat - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2017)
A study was initiated near Garden City, KS, in 2016, comparing the weed control of several herbicide treatments applied preemergence and post-harvest for kochia control in wheat. Clarity (dicamba) with any premix partner applied preemergence provided less than 30% kochia control at evaluations conducted on July 25 and August 12, 2016. The addition of glyphosate plus Distinct (dicamba + diflufenzopyr) postemergence increased control 45 to 66% compared to preemergence treatments alone on July 25 and August 12. However, all treatments receiving a postemergence application controlled kochia similarly on August 12.
Keywords: Residual control; sequential applications